Edukasi Penggunaan Obat Rasional pada Gangguan Saluran Pencernaan Berbasis Farmasi Komunitas - Akhmad Khusaini; Devi Ristian Octavia; Dimas Prayogo Pangestu; Cindy Prassiska; Zumrotun Nafisah; Abdul Majid (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Gastrointestinal disorders are still common in the community and can reduce quality of life if not properly managed. This problem is influenced by the community's low understanding of healthy lifestyles and rational drug use. This community service activity aims to increase the knowledge of the Dlanggu Village community regarding digestive tract disorders, safe and appropriate drug use, and the implementation of a healthy lifestyle. The activity was carried out through health education using lectures, interactive discussions, and educational media in the form of brochures. Evaluation was carried out using pre-test and post-test questionnaires. This activity was attended by 25 participants from the Dlanggu Village women's religious study group. The evaluation results showed an average increase in knowledge from 82.4% in the pre-test to 91.6% in the post-test. This indicates that the education activity is effective in increasing community understanding and is expected to encourage better and more sustainable health behaviors.